(untitled) (Journal of Academic Research, 2024)
The aim of this study was to evaluate the knowledge of general dental practitioners, in private and governmental dental clinics in Zliten, regrading the current American Heart Association (AHA) guidelines for infective endocarditis prophylaxis. This surveying was carried out using a descriptive, closed ended questionnaire which was circulated among 200 general dental practitioners in private and governmental dental clinics in Zliten-Libya. Data was analysed using SPSS. The frequency and percentage of respondents were determined using a descriptive statistics. The effect of the work sector and professional experience on responses was evaluated using Chi-square test (P < 0.05). The questionnaire has been completed by 145 general dentists with overall response rate of 72%. The majority of respondents recommended antibiotic prophylaxis for prosthetic heart (92.4%) followed by rheumatic heart disease (89%), mitral valve prolapse (85.5%), history of infective endocarditis attack (84%), bypass surgery (76.5%), patient with pacemaker (70.3%) and peripheral vascular grafts with patches (69%). 84% of participants advocated antibiotic prophylaxis for teeth extraction followed by abscess drainage (80%), endodontic treatment (79%) and apicoectomy (64%). 50.7% and 46.2% of respondents identified the correct prophylactic regimen for patients not allergic and allergic to penicillin, respectively. 60% of participants used multiple antibiotic doses for endocarditis prophylaxis.